2010
DOI: 10.1016/j.geb.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Perception of probabilities in situations of risk: A case based approach

Abstract: This paper tries to provide a preliminary description of the mental process individuals experience in their attempt to comprehend stated probabilities of simple lotteries.The evaluation of probabilities is based on three main components: lotteries encountered in the past, the realizations of these lotteries, and the similarity between stated probabilities. A probability is evaluated based on the experienced relative frequencies of outcomes that had that stated probability, as well as outcomes of other lotterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…2g, gives a curve like these two but more pronounced. This is consistent with the common empirical finding that attitudes towards uncertainty are like those towards risk, but more pronounced (Abdellaoui et al 2005;Fellner 1961 p. 684;Gayer 2010;Hogarth and Einhorn 1990;Kahn and Sarin 1988 p. 270;Kahneman and Tversky 1979 p. 281;Kilka and Weber 2001;Machina 1982 p. 292;Weber 1994 p. 237/238). In other words, the effects of ambiguity (matching probabilities) reinforce those of risk.…”
Section: Properties Of Matching Probabilities (Ambiguity Attitude)supporting
confidence: 87%
See 1 more Smart Citation
“…2g, gives a curve like these two but more pronounced. This is consistent with the common empirical finding that attitudes towards uncertainty are like those towards risk, but more pronounced (Abdellaoui et al 2005;Fellner 1961 p. 684;Gayer 2010;Hogarth and Einhorn 1990;Kahn and Sarin 1988 p. 270;Kahneman and Tversky 1979 p. 281;Kilka and Weber 2001;Machina 1982 p. 292;Weber 1994 p. 237/238). In other words, the effects of ambiguity (matching probabilities) reinforce those of risk.…”
Section: Properties Of Matching Probabilities (Ambiguity Attitude)supporting
confidence: 87%
“…This agrees with the common finding that uncertainty amplifies phenomena found under risk. Several studies have observed a-insensitivity in the gain domain (Abdellaoui et al 2005;Fellner 1961 p. 684;Gayer 2010;Kahn and Sarin 1988 p. 270;Kahneman and Tversky 1975 p. 15 2nd para; Kahneman and Tversky 1979 p. 281 lines −6/−5 and p. 289 l. 5-6; Kilka and Weber 2001;Viscusi 1989;Weber 1994 pp. 237-238).…”
Section: Summary and Discussion Of Results Of Experiments Amentioning
confidence: 99%
“…In this paper, CBR techniques are approached together with probabilistic and fuzzy set-based modeling. Other approaches such as [14], also assess probabilities based on the frequencies of past cases. In [5], authors compare a probabilistic CBR approach with other well-known classification algorithms.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…However, since both papers consider a finite set of acts, neither of them addresses the impact of the curvature of the similarity function on behavior. Similarity functions defined on uncountable sets are still largely unstudied, except for Gayer (2003).…”
Section: Discussionmentioning
confidence: 99%